Influence of Environmental Conditions and Paving Methods on the Cooling Process of Newly Paved Asphalt Pavement. Issue 1 (February 2021) - Chen, J.Z.; He, L.
Abstract: A newly laid repaired asphalt pavement must be cooled sufficiently before opening to traffic. By using the finite element simulation model, this paper simulates and analyses the temperature distribution during the cooling process of the repaired asphalt layer under different weather conditions, wind speeds and paving methods, and puts forward some suggestions for the determination of the traffic opening time. The results show that when the surface temperature of the repaired pavement drops to the temperature required by the specification, the internal temperature is still higher than the surface temperature. Simply determining the time of opening traffic according to the road surface temperature will cause premature destruction of the asphalt layer. This situation can be avoided when the internal temperature of the repaired asphalt layer is used as the guide for traffic opening. It is easier to meet the requirements of opening to traffic when paving at night. Compared with single-layer paving strategy, the internal temperature of the pavement drops faster under double-layer paving strategy, but the difference is not so obvious.